praktik jual beli tanah menggunakan kwitansi tanpa akta ppat: dampak hukum dan kendala peralihan hak (studi kasus putusan nomor 10/pdt.g/2024/pn.lht) - Fattiah Namiroh; Arsin Lukman (Media Bina Ilmiah, 2025)
The practice of land sale and purchase in Indonesia should comply with land law provisions, requiring a sale and purchase deed issued by a Land Deed Official (PPAT). However, in reality, many land transactions are conducted solely based on a receipt without a PPAT deed, leading to various legal issues. This study aims to analyze the validity of receipts as evidence in land sale transactions and the legal protection available to buyers in transactions without a PPAT deed. This research employs a normative juridical method, using a statutory approach and a case study of Decision Number 10/Pdt.G/2024/Pn.Lht. The findings indicate that while a receipt can serve as proof of transaction, its legal strength is significantly weaker than an authentic deed. Consequently, buyers lack legal certainty regarding land ownership transfers and are at risk of ownership disputes. Additionally, limited legal knowledge and the perception of high administrative costs are the main reasons why people still engage in transactions without a PPAT deed. Therefore, increasing public legal awareness and simplifying administrative procedures for executing sale and purchase deeds are essential to ensuring legal protection and certainty over land rights.